PENGEMBANGAN MOBILE LEARNING BERBASIS ANDROID PADA TOPIK BENTUK ALJABAR UNTUK SISWA KELAS VII SMP - ILMI AULIA SARI (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study is one of the innovations in the field of mathematics learning by utilizing the latest technology.  Coinciding with the COVID 19 pandemic, students and teachers need a mathematics tools that make it easier for them to access it with an android smartphone. This is the reason of Android-based mobile learning is designed. This research begins with analysing students and teacher needs, then analysing curriculum and concept. Then, designing mobile learning and doing self-evaluation. The next stage is an expert review to measure the validity of mobile learning. The next process is one-to-one evaluation and small group evaluation, that was carried out to measure the practicality of mobile learning. The result of all these stages is valid and practical mobile learning. Keywords — mobile learning, algebraic expression, mathematics apps